ANALISIS PENGARUH ATRAKSI, AKSESIBILITAS, AMENITAS TERHADAP MINAT KUNJUNGAN WISATAWAN DI DESTINASI WISATA SARASAH TANGGO NAGARI SARILAMAK, KABUPATEN LIMA PULUH KOTA - Muhammad Ridwan; Jon Kenedi (CV. Adiba Aisha Amira, 2025)
The main objective of this research is to examine and evaluate the extent to which the attractiveness, accessibility and facilities of the Sarasah Tanggo tourist location in Nagari Sarilamak, Limapuluh Kota Regency influence the possibility of visiting the public. A correlational strategy centered on quantitative analysis was used in this research. A total of ninety-six tourists were surveyed using Probability Sampling techniques. Methods such as surveys, participant observation, and documentation are used to collect data. Data analysis methods often use a series of tests, such as testing the reliability and validity of research instruments, as well as testing the classic assumptions of normality, autocorrelation, multicollinearity and heteroscedasticity. Apart from that, the R^2 Coefficient of Determination Test, Multiple Linear Regression Analysis Test, and Hypothesis Testing procedures in the form of Simultaneous Test/F Test and Partial Test/T Test were used. Software from IBM, SPSS Statistics 24, was used to carry out the experiment. The findings of this research indicate that the beauty variable has a significant effect on the tendency of tourists to visit Sarasah Tanggo. The tendency of tourists to visit the Sarasah Tanggo tourist destination is not significantly influenced and predicted by accessibility and facility criteria. Attraction, accessibility and facilities all work together to make the Sarasah Tanggo tourist area increasingly attractive to potential visitors.